O parto além do gênero: a violência obstétrica contra mulheres negras em uma perspectiva interseccional - Miranda, Rafaela Del Castanhel (2024)
This dissertation proposes to reflect on obstetric violence against Black women in Brazil, from the perspective of intersectionality between gender and race. By investigating this complex relationship, we seek to understand how power dynamics and discrimination manifest in specific ways for Black women during pregnancy, childbirth, and postpartum. The research aims to demonstrate that obstetric violence is not just a gender issue but is also profoundly marked by racism. The main objective is to analyze how obstetric violence disproportionately affects Black women. In the research, intersectionality is used as a category of analysis to highlight how gender and race identities interact and overlap, resulting in unique experiences of oppression, as evidenced in the accounts collected through questionnaires, where black women share their experiences of pregnancy, childbirth, and the postpartum period. Additionally, the study will seek to historically contextualize obstetric violence, exploring how discriminatory practices have deep roots in the history of medicine and society, perpetuating inequalities to this day. By bringing these issues to light, we hope to contribute to awareness and the promotion of more fair and humane obstetric practices that respect the dignity and rights of Black women